AB0997 When is hand osteoarthritis erosive? demographic and radiographic features. (23rd January 2014) - Addimanda, O.; Mancarella, L.; Ramonda, R.; Fioravanti, A.; Pignotti, E.; Meliconi, R.
Abstract : Background: Increasing clinical and scientific interest has recently been raised on hand osteoarthritis (HOA); a peculiar subgroup of patients experiment more severe symptoms and characteristic structural damage in the joints (central erosion type lesions - CE). No agreed criteria have been established about the number of erosive joints necessary for the definition of erosive disease. So far reports have been published utilizing both the one erosive joint and the two erosive joints criteria (1-2) Objectives: To evaluate clinical and radiographic features of HOA patients divided into three groups: a)-without CE joint (CEJ), b)-with one CEJ, c)-with at least two CEJ. Methods: 419 patients with HOA were enrolled; on the basis of the presence of central erosion in IP joints they were divided into the three groups. Demographic (gender, age, age of disease onset), clinical (BMI) and radiographic features [Kellgren & Lawrence (K&L) and Kallman's scores obtained from radiographs of both hands] from all patients were recorded. In addition we evaluated the presence of marginal erosions (ME). Results: While significant differences were found between group b and group c in all evaluated items [Age, mean ± sd (95%CI) =67.3±6.7 (66.9-67, 7) vs 68.9±8.0 (68.7-69.1); Age at disease onset, mean ± sd (95%CI) =56.0±9.9 (55.4-56.6) vs 53.7±9.4 (53.4-54.0); Disease duration, mean ± sd (95%CI) =7.9±6.5 (7.5-8.4) vs 11.3±8.7 (11.0-11.5); Total Kallman, mean ± sd (95%CI) =83.2±17.3 (76.5-89.8) vs 98.7±2.4 (95.8-101.6); K&L, mean ± sd (95%CI) =22.5±13.0 (18.5-26.6) vs 33.9±13.1 (32.1-35.7); ME, %(n) =19.5 (198/1016) vs 33.9 (1667/4912), p<0, 0005 for all evaluations], we found no significant difference between group a and group b as far as age at disease onset and K&L score are concerned [Age, mean ± sd (95%CI) =67.0±9.2 (66.7-67.3) vs 67.3±6.7 (66.9-67, 7), p=0.105; Age at disease onset, mean ± sd (95%CI) =56.3±10.0 (55.9-56.6) vs 56.0±9.9 (55.4-56.6), p=0.78; Disease duration, mean ± sd (95%CI) =6.2±6.2 (6.0-6.4) vs 7.9±6.5 (7.5-8.4), p<0.0005; Total Kallman, mean ± sd (95%CI) =71.9±18.8 (68.4-75.5) vs 83.2±17.3 (76.5-89.8), p=0, 011; K&L, mean ± sd (95%CI) =19.4±14.3 (17.3-21.6) vs 22.5±13.0 (18.5-26.6), p=0.457; ME, %(n) =10.6 (349/3295) vs 19.5 (198/1016), p<0.0005]. Conclusions: Since patients without CEJ and patients with only one CEJ had similar values of two relevant features (age at disease onset, K&L score) we suggest that the definition of erosive disease should be confined to patients with at least two CEJ. References: Kwok WY, Kloppenburg M, Rosendaal FR, van Meurs JB, Hofman A, Bierma-Zeinstra SM. Erosive hand osteoarthritis: its prevalence and clinical impact in the general population and symptomatic hand osteoarthritis. Ann Rheum Dis 2011;70:1238-42. Epub 2011 Apr 6 Punzi L, Ramonda R, Sfriso P. Erosive osteoarthritis. Best Pract Res Clin Rheumatol 2004;18:739-58. Disclosure of Interest: None Declared